Herz und mund und tat und terrorismus (heart, mouth, deed, and terrorism). Issue 4 (2nd October 2018) - Tsuboi, Hideto; Murphy, Alexander
ABSTRACT: Since the beginning of the twentieth century, the efforts of a terrorism that makes revolution its goal have sprung from the dream of unity between words and action. In Ōe Kenzaburō's linked texts, "Seventeen, " we find a depiction of a terrorist, or "political youth" who dreams of attaining a "peak orgasm" in communion with the "Pure Emperor." Moreover, for this youth, "terrorism" means an action undertaken by the self at the very moment of coitus between action and words. It is proper that the terrorist should be transformed from a historical anonym to a subject of language through action (prior to carrying out terror he or she cannot appear as a subject of speech). In the linked text of "A Political Youth Dies, " however, the young man's action is obliterated in the flood of images coming from television, and he is stripped of language. In this sense, the youth's situation can be seen as homologous with the terrorism that is bare action stripped of speech, pervasive in our twenty-first century present. A volume containing the translation of "A Political Youth Dies" into German, together with the original Japanese text, has now appeared. Thanks to this publication, we can at last read the original Japanese text. It is now time for us, who have been "deprived of [this] text" for so long, to turn our attention to it.